2005
DOI: 10.1038/sj.bmt.1705148
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative allogeneic hematopoietic stem cell transplantation for Philadelphia chromosome-positive acute lymphoblastic leukemia in adults: significant roles of total body irradiation and chronic graft-versus-host disease

Abstract: Summary:Disease-free survival in Philadelphia chromosome-positive ALL (Ph þ ALL) is very poor, and allogeneic hematopoietic stem cell transplantation (allo-HSCT) is currently considered the only procedure with curative potential. To identify factors affecting transplant outcome, we analyzed the data from 197 Ph þ ALL patients aged 16 years or older who had undergone allo-HSCT. The 5-year survival rates were 34% for patients in first complete remission (CR), 21% for those in second or subsequent CR, and 9% for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 31 publications
(21 reference statements)
2
31
0
2
Order By: Relevance
“…The latter can be explained by the well-known poor GVT effect for high-risk AL, including blast crisis of CML and myeloma. 2 Such results are not completely surprising 10,[13][14][15][16][17][18][19] reflecting also the dismal response of very fast-growing hematological diseases as well as the higher toxicity of the procedure in heavily pre-treated patients. However, these data may be tempered as better outcomes may be obtained in some selected subgroups according to pre-transplant variables, as previously described by Duval et al 10 in patients with active relapsed/refractory AL after myeloablative conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The latter can be explained by the well-known poor GVT effect for high-risk AL, including blast crisis of CML and myeloma. 2 Such results are not completely surprising 10,[13][14][15][16][17][18][19] reflecting also the dismal response of very fast-growing hematological diseases as well as the higher toxicity of the procedure in heavily pre-treated patients. However, these data may be tempered as better outcomes may be obtained in some selected subgroups according to pre-transplant variables, as previously described by Duval et al 10 in patients with active relapsed/refractory AL after myeloablative conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…13,[16][17][18] In a retrospective review of 197 patients with Ph + ALL who underwent allogeneic SCT, the 5-year survival rates were 34% for patients in first CR, 21% for those in second or subsequent CR, and 9% for those with active disease (P < .0001). 19 Multivariate analysis identified that younger age, CR at the time of SCT, conditioning with total body irradiation, and an HLA-identical sibling donor were factors associated with improved survival. Newer modalities such as nonmyeloablative conditioning regimens or donor cells derived from umbilical cord blood have increased the applicability of allogeneic SCT, but a significant proportion of patients remain ineligible for this potentially curative approach and are in need of novel therapy.…”
Section: Allogeneic Stem Cell Transplantation For Phmentioning
confidence: 99%
“…Thus, patients who developed extensive chronic GVHD had better survivals (P = .0217), and those who developed grade III-IV acute GVHD had worse survivals (P = .0023) than did the others. 36 Immunotherapy with donor lymphocyte infusion (DLI) and imatinib appears to be well tolerated but is rarely and in general only transiently effective. A rationale for the combined use of DLI and second-generation TKIs such as nilotinib is suggested by case reports, but prospectively collected data are as yet not available.…”
Section: Allogeneic Stem Cell Transplantation With Myeloablative Condmentioning
confidence: 99%
“…An intensified preparatory regimen consisting of SCT after fractionated total body irradiation and etoposide with or without cyclophosphamide was explored by Kröger et al 34 and Laport et al 35 TRM was mainly due to infections or GVHD, and was higher in patients with more advanced disease. 35,36 Factors affecting event-free and overall survival likewise included disease status (CR1 vs > CR1) and higher age, with a cutoff at approximately 30 years, at the time of transplantation. [32][33][34][35] Thus, while these intensified preparatory regimens confer long-term survival in a subset of patients with Ph + ALL, relapse and TRM remain important causes of treatment failure, making success unlikely in patients with more advanced disease.…”
Section: Allogeneic Stem Cell Transplantation With Myeloablative Condmentioning
confidence: 99%